PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KETERAMPILAN MENULIS SURAT DINAS SISWA KELAS VIII SMP NEGERI 16 PADANG - Septiani, Cyntia; Emidar, Emidar; Noveria, Ena (Universitas Negeri Padang, 2018)
This study has three objectives as follows. (1) Describing the level of writing official letter to the grade of VIII SMP Negeri Padang 16 before using the model of problem based learning. (2) Describing the level of writing official letter to the grade of VIII SMP Negeri Padang 16 after using the model of problem based learning. (3) Describing the influence of problem based learning model to write official letter to grade VIII SMP Negeri Padang 16 after using the model of problem based learning. Type of this research is quantitative with the experimental method. Based on the data analysis, the use of model of problem based learning to the grade of VIII SMP Negeri Padang 16. Kata kunci : pengaruh, model problem based learning, keterampilan menulis surat dinas